A roadmap to understanding interoceptive awareness and post-traumatic stress disorder: a scoping review - Leech, Kelly; Stapleton, Peta; Patching, Alan (Frontiers in Psychiatry, 2024)
The concept of interoception has existed since the beginning of the 1900s. It is suggested that humans can observe feelings arising from the body that allows them to develop a sense of their emotional status and physical condition. The term interoceptive awareness appears to originate with clinicians working with individuals who had experienced trauma, in particular Post Traumatic Stress Disorder (PTSD). The purpose of this scoping review was to provide an overview of the existing literature surrounding the combination of these two themes: interoceptive awareness and PTSD. A total of 226 articles were initially screened and 52 articles were retained for comprehensive review. Nine articles were excluded, resulting in 43 studies included in the review. The review aimed to answer: (a) how is interoceptive awareness defined? (b) how is interoceptive awareness measured? (c) what is the function of interoceptive awareness? (d) is there/what is the relationship between interoceptive awareness and PTSD? The scoping review identified nine terms that are used synonymously throughout the literature surrounding interoceptive awareness and PTSD, and three primary ways in which interoceptive awareness is measured in relation to PTSD. The primary function documented was the role interoceptive awareness played in an individual’s ability to regulate their emotions, and the most common and compelling function emerging was the association with emotion regulation. The evidence supports the utilisation of a definition of interoceptive awareness to include one that includes the quality of cognitive appraisal and focuses on the adaptive mindful approach to internal physical sensations as opposed to the heightened ruminative self-focus. Limitations and future research are suggested.